Peran Sektor Pemerintah dan Swasta dalam Perkembangan Destinasi Wisata di Kabupaten Pulau Morotai - Enggar Dwi Cahyo; Wiendu Nuryanti (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2018)
Morotai tourism destination is located in North Molucas Province and directly bordering with Philippines. Morotai tourism destination is one of the ten national priority tourism destination of the Republic Indonesia. Kabupaten Pulau Morotai also has one area that is used as a Special Economic Zone based on the development of tourism industry. Tourism development in this region involves many institutions, both from the government sector and from the private sector. This research was proposed to nd out about: (1) Fnding out about the role of public and private sector in the development of Morotai tourism destination, (2) Finding out the impact of all programs which run by all sector for the Morotai tourism destination area. This study uses a qualitative approach with primary data collection using data collection techniques of observation, interviews, and institutional surveys to be able to explore the phenomena that occur at the research location. Interview respondents were determined based on purposive sampling with the selection of respondents based on their respective capacities in the development of tourism destination in Kabupaten Pulau Morotai and supported by secondary data that was deemed appropriate to the research context. Data analysis techniques used descriptive analysis techniques to see sharper phenomena. This study produces the following ndings: (1) At present Central Government still dominates the course of destination development programs in Kabupaten Pulau Morotai, 2) One of the main impacts that occur is the improvement of infrastructure that supports tourism activities in Kabupaten Pulau Morotai. This condition shows that the Morotai Tourism Destinations have potential chance to become the core of tourism industry in North Moluccas Province.